2022
DOI: 10.3390/cells11142175
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Immunomodulatory Aspect of Mesenchymal Stem Cells for Treatment of Severe Coronavirus Disease 19

Abstract: Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) is an enveloped, positive sense, single stranded RNA (+ssRNA) virus, belonging to the genus Betacoronavirus and family Coronaviridae. It is primarily transmitted from infected persons to healthy ones through inhalation of virus-laden respiratory droplets. After an average incubation period of 2–14 days, the majority of infected individuals remain asymptomatic and/or mildly symptomatic, whereas the remaining individuals manifest a myriad of clinical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 133 publications
0
3
0
Order By: Relevance
“…MSCs are ACE2-negative, and therefore they are resistant to SARS-CoV-2 infection and retain their immunomodulatory activities when encountering the virus [ 185 , 186 ]. This important feature favors MSC therapeutic use in COVID-19 [ 187 ]. Interaction with innate immune cells, especially Mφs, and molecules secreted by MSCs and Mφs, described above, could dampen immune hyper-activation in SARS-CoV-2 infection.…”
Section: Therapeutic Potential Of Msc-mφ Interaction and Lung Injury ...mentioning
confidence: 99%
“…MSCs are ACE2-negative, and therefore they are resistant to SARS-CoV-2 infection and retain their immunomodulatory activities when encountering the virus [ 185 , 186 ]. This important feature favors MSC therapeutic use in COVID-19 [ 187 ]. Interaction with innate immune cells, especially Mφs, and molecules secreted by MSCs and Mφs, described above, could dampen immune hyper-activation in SARS-CoV-2 infection.…”
Section: Therapeutic Potential Of Msc-mφ Interaction and Lung Injury ...mentioning
confidence: 99%
“…Moreover, VEGF accelerated M2 macrophage infltration and disrupted the airway epithelial barrier in lung tissues of asthmatic animals [48][49][50][51]. Emerging evidence also displayed that VEGF has associations with thromboembolism and tissue injury/repair in COVID-19 and viral infection, indicating the promotion of secondary airway infammation [52][53][54]. Te results of this study showed that HHAE signifcantly reduced the expression levels of p38 MAPK, PI3K, Akt, and VEGF mRNA and protein in lung tissue of asthmatic mice, suggesting that the mechanism of HHAE alleviating asthma infammation is related to the inhibition of the p38 MAPK/PI3K signaling pathway.…”
Section: Discussionmentioning
confidence: 97%
“…MSCs naturally produce a variety of active ingredients with trophic, immunomodulatory, pro-regenerative, anti-inflammatory, pro-angiogenic, and anti-apoptotic properties [ 6 ]. MSCs regulate immune function in a paracrine manner by producing immunomodulatory factors such as transforming growth factor (TGF), hepatic growth factor (HGF), interleukin (IL)6, and IL-10, as well as pro-angiogenic factors like basic fibroblast growth factor (bFGF) and placental growth factor (PGF) [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%